Apple-peel atresia presenting as foetal intestinal obstruction - Ashok Yadavrao Kshirsagar; Sushma Rajaram Desai; Mayur Anant Nagvekar; Gaurav Om Prakash Vasisth (Wolters Kluwer Medknow Publications, 2011)
Apple-peel atresia or Type 3 jejuno-ileal atresia (JIA) is an uncommon cause of foetal intestinal obstruction. Bowel obstruction in the foetus is diagnosed on the prenatal ultrasonography only in 50% cases. We report a case in which foetal intestinal obstruction was diagnosed on prenatal ultrasonography. The child showed signs of intestinal obstruction on day one after birth, for which an exploratory laparotomy was performed. Type 3 JIA was found for which resection of atretic segments with jejuno-ascending colon anastomosis was preformed.